El fraude fiscal en la corporación aduanera ecuatoriana: análisis de las causas y promulgación de nuevas alternativas para prevenirlo - Diaz, Lourdes (2009)
This thesis is based on the analysis of the Fraud pertaining to Customs Duties tariffs and taxes Evasion in Ecuador. Being the Tax evasion a Customs phenomenon that not only affects the country’s revenues but also originates a distortion of the General Tax System and the economical situation of the country itself. One of the primary effects is the unfair competition originated from evaders. With this research we have also identified the more common customs infractions, studied the relationship between tax increases and tax evasion, concluding that higher tax rates provoke a higher tax evasion and how much this evasion of internal taxes such as the VAT has affected the government and to the International trade.